Pengaruh Program Gopay Payday Sebagai Customer Relationship Management Terhadap Brand Equity Gojek (PT. Aplikasi Karya Anak Bangsa) - Viana Eka Wardani; Euis Komalawati; Alfirahmi Alfirahmi (LUGAS Jurnal Komunikasi, 2020)
Customer Relationship Management (CRM) is an approach to identifying, attracting, and improving relationships between companies and customers. Karya Anak Bangsa Inc. (Gojek) with its application Gopay, gave rise "Gopay Payday" program as a customer relationship management to decide the brand equity level of Gopay application users. Brand Equity plays an important role because brand equity forms the name of the company's image and reputation, even as determining to make company goals. The purpose of this research analyzes the influence of the Gopay Payday program as a customer relationship management on Gojek brand equity (Karya Anak Bangsa Inc.). This research uses quantitative descriptive, and the method is a purposive sampling technique within 100 respondents as the sample. The data analysis technique used SPSS 25.0 for Windows computer software tools. The results of this study show that there is a significant influence on customer relationship management by 24.2% against brand equity. It means the better the Customer Relationship Management, the Brand Equity of the company will increase.